Guidelines on treatment of patients with arterial hypertension comorbid with metabolic disorders and diabetes mellitus type 2 - I. E. Chazova; M. V. Shestakova; Yu. V. Zhernakova; T. N. Markova; N. V. Mazurina; M. V. Yezhov; O. Yu. Mironova; A. Yu. Litvin; E. M. Elfimova; N. V. Blinova; O. Yu. Sukhareva; A. S. Ametov; et al. (Системные гипертензии, 2020)
Guidelines on treatment of patients with arterial hypertension comorbid with metabolic disorders and diabetes mellitus type 2